2008
DOI: 10.1097/cmr.0b013e3282f60097
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin inhibits growth via apoptosis and the induction of cell cycle arrest in human melanoma cells

Abstract: Competitive inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A reductase (the statins) that inhibit the synthesis of mevalonic acid are in wide use for treatment of hypercholesterolemia. Although antitumor effects on a variety of cell types have been reported for statins, the effect of simvastatin (one of the statins) on human melanoma cell lines is not known. Here, we report antitumor effects of simvastatin on human melanoma cell lines. We treated human melanoma cell lines, A375M, G361, C8161, GAK, and MMAc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 51 publications
7
45
0
4
Order By: Relevance
“…Our observations and published data also demonstrated that monotreatment with statin induced pronounced apoptotic death in some melanoma cell lines only at relatively high doses (5–20 μM) [44]. Animal experiments with the B16F10 mouse melanoma model exhibited a suppression of tumor growth by treatment with 1.6 μM simvastatin [45].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our observations and published data also demonstrated that monotreatment with statin induced pronounced apoptotic death in some melanoma cell lines only at relatively high doses (5–20 μM) [44]. Animal experiments with the B16F10 mouse melanoma model exhibited a suppression of tumor growth by treatment with 1.6 μM simvastatin [45].…”
Section: Discussionsupporting
confidence: 73%
“…Even though proapoptotic effects of statins for melanoma cells have been previously reported in several publications [44, 55, 56], sensitization of melanoma cells to TRAIL-induced apoptosis by statins, which was investigated in our study, potentially could be a new modality for melanoma therapy. It was especially important, that combined treatment of statin and TRAIL was also quite effective for killing BRAF wt melanoma cell lines, such as WM852 and FEMX (see Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Despite promising findings stemming from in vitro and animal studies [3][4][5][6][7][8][9], the present quantitative synthesis of 16 RCTs provides no evidence for an association between statin use and the risk of melanoma. Our results are in accord with recent metaanalyses on the association between statin use and other site-specific cancers.…”
Section: Discussionmentioning
confidence: 77%
“…In vitro and animal studies have supported a potential protective role of statins through pleiotropic antiinflammatory, immunomodulatory, and antiangiogenesis mechanisms. In particular, statins have been shown to induce melanoma cell apoptosis, to inhibit proliferation and invasion, and to prevent activation of key proteins for cell cycle regulation [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This effect was mediated by direct interference with RAS functions (Grana et al, 2002) and G 1 arrest of the cell cycle (Sivaprasad et al, 2006;Saito et al, 2008;Javanmoghadam-Kamrani and Keyomarsi., 2008), in addition to the arrest in G 2 phase induced by radiation.…”
Section: Statins In Cancer Treatmentmentioning
confidence: 99%